Nonrecurrent 17p duplications in two patients with developmental and neurological abnormalities - Lee, Ah Jin; Pi, Byung Kwon; Nam, Soo Hyun; Kim, Hyun Su; Choi, Byung-Ok; Chung, Ki Wha (Human genome variation, 2025)
Variable copy number variations (CNVs) in the short arm of chromosome 17 are associated with many neurodevelopmental disorders, including Charcot–Marie–Tooth disease type 1A, Potocki–Lupski syndrome and Yuan–Harel–Lupski syndrome. Here we examined CNVs in two sporadic cases of developmental abnormalities, brain impairment and peripheral neuropathy. We identified novel duplications of approximately 14.1 Mb at 17p11.2–p13.1 (containing PMP22 and RAI1 ) and 17.6 Mb at 17p11.2–p13.3 ( YWHAE , PAFAH1B and PMP22 ) in each patient. Both duplications were suggested to be produced by de novo mutations of paternal origin. This study suggests that CNVs at 17p should be examined in patients with peripheral neuropathy as well as developmental and brain abnormalities.